Does luck egalitarianism lose its appeal in the face of genetic engineering? - Theophilopoulou (Αρετή Θεοφιλοπούλου), Areti (Bioethica, 2015)
It has been suggested that the era of genetic interventions will sound the death knell for luck egalitarianism, as it will blur the line between chance and choice, on which theories of distributive justice often rest. By examining the threats posed to these theories, a crucial assumption is exposed; it is assumed that a commitment to the neutralisation of the effects of luck implies the endorsement of even the most morally controversial enhancements. In antithesis, I argue that an attractive theory of luck egalitarianism, Dworkinian liberal equality, enables us to deduce plausible implications for genetic engineering. By focusing on the abstract moral commitments at the heart of Dworkin’s theory, a twofold purpose is served. First, they reveal in what ways the criticisms misfire, thereby safeguarding luck egalitarianism. Second, Dworkinian luck egalitarianism is further strengthened, as it produces plausible guidelines for public policy on genetic engineering in liberal societies.